Novel thin film nanocomposite membranes incorporated with polyoxovanadate nanocluster for high water flux and antibacterial properties. (14th January 2020) - Amini, Mojtaba; Shekari, Zahra; Akbari, Ali; Naslhajian, Hadi; Sheykhi, Ayda; Karimi, Esmaeil; Gautam, Sanjeev; Chae, Keun Hwa
Abstract : Using interfacial polymerization (IP) of m‐phenylenediamine aqueous solution containing polyoxovanadate nanoclusters (POV) and trimesoyl chloride (TMC) in organic solution, we fabricated a novel polyamide (PA)‐ polyoxovanadate nanocluster (POV) nanocomposite membranes (PA‐POV TFN). The chemical structures and morphologies of the synthesized membranes were characterized by Fourier transform infrared (FTIR) spectroscopy, atomic force microscope (AFM), scanning electron microscopy (SEM) and water contact angle measurements. Experimental results showed that the performances of PA‐POV TFN membranes are remarkably dependent on POV incorporation in the membranes, which could be controlled by using different amounts of POV particles. Moreover, the PA‐POV TFN membranes illustrated outstanding antibacterial properties against Gram‐negative E. coli. On the other hand, the incorporation of various amounts of POV in the membranes improved the membrane separation performances (water flux and salt rejection) as well as the antibacterial activity in FO process as compared to the original thin‐film composite (TFC) polyamide membrane. Abstract : Novel thin‐film nanocomposite membranes were incorporated with polyoxovanadate nanocluster for using in forward osmosis (FO) process.